EXPLORING THE EXPERIENCES OF NON-NATIVE ENGLISH TEACHERS IN BUILDING STUDENT SPEAKING SKILLS - Hakim, Waliyul (FKIP UM Pontianak, 2025)
The ability to communicate effectively in English is essential in today’s globalized world. however, many students continue to face difficulties in speaking confidently. This study aims to explore the experiences of non-native English teachers (NNESTs) in developing students’ speaking skills, focusing on the challenges they encounter and the strategies they employ in Kampung Inggris Pare, Indonesia. A qualitative research design with a phenomenological approach was applied, involving three NNESTs as participants. Data were collected through semi-structured interviews and analyzed thematically using NVivo 12 software. The findings indicate that the teachers encountered several challenges, including students’ limited vocabulary, speaking anxiety, low motivation, and varied proficiency levels within a single classroom. To address these challenges, the teachers implemented various strategies such as creating a supportive classroom environment, providing positive reinforcement, selecting engaging and contextually relevant speaking topics, and promoting peer collaboration. Emotional support and teacher empathy were also found to be essential in enhancing students’ speaking confidence. This study emphasizes the crucial role of NNESTs in fostering inclusive, engaging, and motivational learning environments. The findings contribute to a deeper understanding of how teacher identity and socio affective strategies influence students’ speaking development and offer valuable insights for improving English speaking instruction in EFL contexts.